EMERGING CHALLENGES IN IMPLEMENTING UNIVERSAL HEALTH COVERAGE DUE TO COVID-19 IN INDONESIA - Rosyidah Rosyidah (Universitas Ahmad Dahlan, 2022)
The goal of Universal Health Coverage (UHC) means a situation in which all individuals and communities have access to health services, whenever and wherever they need them, without financial barriers to obtaining them. UHC covers a wide range of essential health services, from promotion, prevention, treatment, care, rehabilitation, and palliative care for patients with chronic diseases. On the other hand, the COVID-19 Pandemic is devastating national health systems in countries that have strived to provide UHC, hampering their efforts to fulfill the ethos of universal health coverage, which is to